A numerical study of two different specimen fixtures for the modified compact tension test – their influence on concrete fracture parameters (Fracture and Structural Integrity, 2015)
The modified compact tension test (MCT) may represent a new test configuration for the performance of static and other kinds of fatigue tests on concrete-like materials. Core drilling can be employed to obtain specimens which are cylindrical in shape and have a standard diameter of 150 mm, this being appropriate for the determination of the residual life of structures. This contribution focuses on the evaluation of MCT specimen fracture behavior during static tests. Cracks evolution are simulated numerically using ATENA finite element (FE) software, while the results are represented as L-COD diagrams, i.e. load vs. crack opening displacement measured on the loading axis. After numerical calculations, the results for two different fixtures are compared and the advantages or drawbacks for each solution are discussed.
Keywords: Modified Compact Tension Test; Fracture Parameters; Cementitious Composites; FEM